Computational development of rubromycin-based lead compounds for HIV-1 reverse transcriptase inhibition - Carlos E.P. Bernardo; Pedro J. Silva (PeerJ, 2014)
The binding of several rubromycin-based ligands to HIV1-reverse transcriptase was analyzed using molecular docking and molecular dynamics simulations. MM-PBSA analysis and examination of the trajectories allowed the identification of several promising compounds with predicted high affinity towards reverse transcriptase mutants which have proven resistant to current drugs. Important insights on the complex interplay of factors determining the ability of ligands to selectively target each mutant have been obtained.